"The Mask Is Ripped Off along with the Skin": Ways of Constructing the Subject in the Political Poetry of the 2010s. (3rd July 2018) - Korchagin, Kirill
Abstract : This article examines recent poems in which speaking subjects of various kinds engage in political speech, arguing that this poetry is distinctly different from earlier political poetry in Russia and especially in the Soviet Union.